The Divine Values in The Development of Legal Science: A Perspective of the Philosophy of Science - Helda Rahmasari; Nur Sulistyo Budi Ambarini; David Aprizon Putra (Al-Syakhsiyyah: Journal of Law and Family Studies, 2025)
This research seeks to explore the divine values in the development of legal science through the lens of the philosophy of science. In the context of humans as social beings created by the Almighty God, law functions as a normative guide to achieve justice and regulate social interactions. This research focuses on two main issues: the influence of divine values on the formation and development of legal science, and the integration of these values to create a balance between legal certainty, utility, and justice. This study employs a qualitative approach using historical and analytical methods. The type of research is a literature study. This research utilizes primary legal materials such as books, scholarly articles, previous academic studies, and other documents discussing divine values, the philosophy of science, and their relationship with legal principles such as justice, utility, and legal certainty. Subsequently, all obtained data is analyzed through qualitative analysis. The findings indicate that divine values play a crucial role in shaping a divinely-oriented legal paradigm that not only prioritises the formal aspects of law but also the moral and spiritual values derived from religious teachings. From this perspective, law is understood as a manifestation of universal divine values, with Pancasila serving as the epistemological framework that ensures the integration of moral principles within Indonesian law. Furthermore, divine values can create harmony between legal certainty, utility, and justice, where the concept of justice is emphasised to be not merely formal but also substantive, reflecting social justice and human dignity as creations of God. This research underscores the importance of divine values as a foundation in the development of legal science that is adaptive to the social dynamics of society.